2021
DOI: 10.29173/jjs143s
|View full text |Cite
|
Sign up to set email alerts
|

C. G. Jung’s Thoughts on the Concepts of Leader and Leadership

Abstract: A review of the written record suggests that C. G. Jung had relatively little to say about leadership. It also appears that the scattered comments he did make on the topic have garnered him little credit. Sensing, however, under-acknowledged value in Jung’s offerings, the authors of the present study curate the various pieces of this material and comment on the relevance of Jung’s thoughts to the field of leadership studies. The authors suggest caution in interpreting his ideas, given the differences between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In one of the most thorough attempts at coupling Jung’s concept with theories on authentic leadership, Ladkin et al (2018: 419) argue that given ‘how central the notion of the self is to authentic leadership theorizing, it seems vital to explore theories of how the self develops into a differentiated individual’. But although Ladkin et al (2018) clarify individuation’s relevance for authentic leadership studies, the current study instead emphasizes humanistic investigations of how ‘the character of a leader grows out of the profoundly difficult, lifelong work of learning about and embracing the complexities of the personal psyche’ (Corlett and Chisholm, 2021: 12). We thus draw inspiration from Ladkin et al (2018) and others to analyze the SGEs of sports leaders and how they have affected their individuation processes in life.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the most thorough attempts at coupling Jung’s concept with theories on authentic leadership, Ladkin et al (2018: 419) argue that given ‘how central the notion of the self is to authentic leadership theorizing, it seems vital to explore theories of how the self develops into a differentiated individual’. But although Ladkin et al (2018) clarify individuation’s relevance for authentic leadership studies, the current study instead emphasizes humanistic investigations of how ‘the character of a leader grows out of the profoundly difficult, lifelong work of learning about and embracing the complexities of the personal psyche’ (Corlett and Chisholm, 2021: 12). We thus draw inspiration from Ladkin et al (2018) and others to analyze the SGEs of sports leaders and how they have affected their individuation processes in life.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Contrasting some humanist theories of leadership, which essentialize identity by seeing the Leader’s Self as a more or less integrated whole waiting to be found through self-actualization and then utilized in practice as e.g., authentic leadership (Clifton, 2018: 623), our study emphasizes the empathic element of humanist approaches to leadership. For example, although Jung commented on leadership ‘in a desultory manner’ (Corlett and Chisholm, 2021: 6), his skepticism towards the ‘guru-disciple’ relationship found in contexts of authority, power, and influence (Jung, 1953: 263–264) encourage us to pursue a reciprocal perspective in touch with Ladkin et al’s (2018) emphasis on leadership as a relational process. By understanding how this relationality works, such as through communicative practices because they are ‘about encounters and relationships as much as it is about the transmission of information’ (Ashman and Lawler, 2008: 254), it can bring new insight to the often-troubled relationship between external leader role expectations and internal leader role identities (Gjerde and Ladegård, 2019: 44).…”
Section: Existentialism Humanism and Leadershipmentioning
confidence: 99%
“…The personal development of the leader. Corlett and Chisholm (2021) have reported the profound connection Jung made between the leader and the leader's individuation (the development of an individual's personality). Similarly, Corlett and Pearson (2003) have suggested that those leaders best equipped to create "organizational wholeness" (a balancing of archetypal forces) are those committed to doing their own inner work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As documented by Corlett and Chisholm (2021), Jung hinted at the idea of leadership in widely scattered comments. Poring over this fragmentary material, I experienced a growing sense that there might be more there than immediately met the eye.…”
Section: Introductionmentioning
confidence: 99%